Institutional quality and agglomeration of fast food multinationals in Latin American cities. (21st August 2017) - Robles, Fernando
Abstract : Purpose: The purpose of this paper is to explore the location decision of multinationals across major cities in Latin America. Based on agglomeration economics and institutional theory, the paper explores whether institutional quality of a city can temper the attraction of agglomeration factors. Design/method/approach: The paper analyzes the geographic dispersion of three global fast-food franchise networks in 45 Latin American cities. The explanatory variables are horizontal aggregation of other multinationals and the institutional quality of a city. The direct and indirect impacts of horizontal agglomeration are explored through negative binomial regression with controls for city population and economic power [gross domestic product (GDP)]. Findings: The key finding is that location choice of fast-food networks is driven principally by market conditions and to a lesser extent by horizontal agglomeration. The institutional quality of a city has a positive influence on the agglomeration of fast-food networks. A city with strong institutional quality makes this relation stronger. Research limitations: Other multinational and national fast-food franchises are not included in the paper. Future studies should include a greater number of global and local fast-food franchisers. Practical implications: The positive reinforcements of agglomeration and strong institution are important for the investment location decision of fast-food multinationals. The institutional quality of the city should be an important consideration in the location decision as it expands regionally and within a country. Smaller cities may not offer the agglomeration advantages of the large metropolitan areas, but their good institutional quality may reduce the business costs for multinationals. Social implications: Large cities in Latin America tend to reap the benefits of agglomeration. As a result, smaller secondary cities struggle to be relevant in generating economic activity and attracting private investments. One strategy to achieve relevance is to build strong and transparent institutions and a solid business environment. Originality/value: The inclusion of institutional quality at the city level as moderation of the agglomeration factors influencing the location decision of a multinational is original. This paper contributes to our understanding of the importance of regional cities in attracting the investment of multinational firms.